THE IMPORTANCE OF USING TECHNOLOGY IN ENGLISH TEACHING AND LEARNING - Masruddin, Masruddin (Institut Agama Islam Negeri Palopo, 2014)
This paper is focused on the description of technology role in English teaching and learning.Â Globalization has created a new world order for doing business.Â New information and communication technologies (ICTs) have dramatically changed the way we live, learn, work, and even think about work.Â The synergy of combining globalization with new technology has had dramatic economic and social impacts include in English language teaching and learning. the role of technology media is needed in learning process where media is not as a tool but as a part of integral in educational system and learning process.Â Furthermore, the use of technology as media inÂ classroom is very helpful.Â Furthermore, media technology can increase the studentsâ interesting in learning process.